2005
DOI: 10.1073/pnas.0504218102
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of oxidized and reduced mitochondrial thioredoxin reductase provide molecular details of the reaction mechanism

Abstract: Thioredoxin reductase (TrxR) is an essential enzyme required for the efficient maintenance of the cellular redox homeostasis, particularly in cancer cells that are sensitive to reactive oxygen species. In mammals, distinct isozymes function in the cytosol and mitochondria. Through an intricate mechanism, these enzymes transfer reducing equivalents from NADPH to bound FAD and subsequently to an active-site disulfide. In mammalian TrxRs, the dithiol then reduces a mobile C-terminal selenocysteine-containing tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
96
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 51 publications
12
96
1
Order By: Relevance
“…2, panel A) (26,38). The recognized role of Tyr 296 (39), acting as a "gate" for NADPH binding, is confirmed in our structure. In fact, the phenolic ring of Tyr 296 , which points toward the re-face of the isoalloxazine ring of FAD in a T-shape configuration (see Structure 1 and also Ref.…”
supporting
confidence: 59%
“…2, panel A) (26,38). The recognized role of Tyr 296 (39), acting as a "gate" for NADPH binding, is confirmed in our structure. In fact, the phenolic ring of Tyr 296 , which points toward the re-face of the isoalloxazine ring of FAD in a T-shape configuration (see Structure 1 and also Ref.…”
supporting
confidence: 59%
“…The allele was designed to allow excision of these first two protein-coding exons (Fig. 1a), which encode conserved amino acids 1-30 that contact flavin-adenine dinucleotide (FAD), are an integral part of the Rossman fold common to NADPH-binding proteins [45,46], and are found in all Txnrd1 mRNA isoforms [40]. Furthermore, when exons 1 and 2 are excised, the first in-frame AUG in the resultant mRNA (Met 70 ) is in a poor context for translation initiation and any polypeptide initiated here would lack both N-terminal active site cysteines (Cys 59 and Cys 64 ) (see below).…”
Section: Design and Production Of Txnrd1-mutant Micementioning
confidence: 99%
“…The structure of the selenenylsulfide motif and its location in the enzyme has so far only been modeled. The prior structure determinations of Sec-to-Cys mutant forms of mammalian TrxR (32,36,37) furthermore revealed that the C-terminal tail seems to be highly flexible, with the configuration of the final C-terminal residues therefore difficult to model with any appreciable certainty.…”
mentioning
confidence: 99%
“…In 2001, the first crystal structure of a Sec-to-Cys mutant of rat TrxR1 was published (32), followed by several structure determinations of similar Sec-substituted mutants, i.e. mutants of mouse TrxR2 (33)(34)(35)(36), human TrxR1 (37) (also as directly deposited PDB entry 2CFY), and the non-selenoprotein orthologue of Drosophila (34,35). These structures as well as additional modeling studies and several extensive biochemical analyses (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) have generated a generally accepted model for the major features of the catalytic mechanism of mammalian TrxRs.…”
mentioning
confidence: 99%